Understanding the Sub-Culture, Challenges and Needs of Persons with Disabilities - Rafidah Aga, Mohd Jaladin; Nasrul Anuar, Abd Razak; Janet Ann, Fernandez (University of Malaya Press, 2021)
Persons with disabilities have long suffered discrimination, causing exclusion from mainstream society. However, the biggest barrier that persons with disabilities face are other people. Many of us are unaware of their challenges and the need to make society more inclusive for persons with disabilities. The first chapter aims to increase people’s knowledge of the issues concerning persons with disabilities. This chapter introduces the concept and different types of disabilities. Discussion on the challenges faced by persons with disabilities as well as their general and specific needs are also included. The discussion implies that there is a need to empower them using a multidisciplinary approach so that they can maximize their daily functioning and ultimately enjoy life to the fullest.